The Relationship of the Attitude to Cheating with Social Beliefs and the Supposed Attitude of Others in High School Students - E.V. Ulybina; A.A. Tokareva (Moscow State University of Psychology and Education, 2024)
Academic dishonesty is a widespread but dangerous phenomenon, as it forms tolerance for fraud in other areas, including through tolerance of the dishonesty of others. The article is devoted to the analysis of the correlation between the subjective assessment of the permissibility of academic dishonesty and belief in a competitive world (BCW), the supposed assessment of peers and adults among schoolchildren, loyal and not loyal to dishonesty. It is considered both the attitude towards cheating itself (active dishonesty), as well as the message about the dishonesty of others and the refusal to help in dishonesty (passive dishonesty). 507 people were recruited for the research, 296 of them girls, aged from 13 to 18 years, average age of 15,6 (±1,38), who completed the questionnaire online. The level of BCW was measured using the questionnaire "Scale of belief in a competitive world, short version" by J. Dakkit adapted by O.A. Gulevich and colleagues. To assess the permissibility of cheating, were used vignettes, which described dishonest behavior and judgments about this behavior. Participants were supposed to assess them on a Likert scale from 1 to 9. Each type of dishonesty (cheating itself, reporting cheating and refusing to help with cheating) was represented by 3 vignettes. The results showed that the assessments of the admissibility of certain aspects of cheating are not related to each other and have a different structure of links with the BCW and the intended assessment of others. The results confirm the data on the greater complexity of honesty compared to dishonesty. For the disloyal, the permissibility of cheating is associated with more factors than for the loyal. Active dishonesty in loyal people is associated with prevalence, in disloyal people – with BCW and the opinion of parents.